Bio-availability of phosphorus fertilizers in acid paddy soils with different P status - GUO Hai-chao; WANG Guang-huo; DING Na; ZHANG Qi-chun (浙江大学学报. 农业与生命科学版)
Pot experiments on three acid paddy soils with different P status were conducted to investigate the effects of P fertilizers on ryegrass growth and changes of soil P fractions after ryegrass planting. The results show that application of P fertilizers increased dry matter weight and P uptake of ryegrass on low-P status soils (NK and CK) by 32.7%-53.0% and 82.4%-151.9%, respectively; on high-P status soil (NPK) by 11.0%-14.0% and 51.1%-65.0%, respectively. Dry matter weight and P uptake of ryegrass on NPK soil were higher than that on NK and CK soil under the same fertilizer treatment. Average agronomic efficiency of P fertilizer (AEP) for KPR500, KPR1000 and SSP22 on three soils were 5.6, 2.5 and 124.2, respectively; average recovery efficiency of P fertilizer (REP) for KPR500, KPR1000 and SSP22 on three soils were 1.0, 0.7 and 21.1, respectively. Compared with the control (no P application), soil available P (Resin-P, NaHCO3-Pi and NaHCO3-Po) increased at different grade on the three soils after P fertilizers application. Soil NaOH-Pi also increased, while soil NaOH-Po was stable and less affected by addition of P fertilizers. Phosphate rock application increased soil HCl-P and Residual-P fractions substantially.